Performance evaluation of buried PVC pipelines for tank irrigation: a case study of Deevanur tank - V. T. Neelmudiyon; V. Preethi; S. Govindarajan (Water Supply, 2023)
Water is vital to life and development in all parts of the world. Since rain or other precipitation is the only source of water, it should be carefully harvested, stored, conserved and managed for the benefit of the largest number by optimizing the use of the amount available. The available water should be utilized judiciously so that the future generation is saved from deterioration stress. This study was conducted in the Deevanur tank located in Tindivanam Taluk in Tamil Nadu, India. The study was carried out in the crop calendar years from 2006–07 to 2017–18. The performance of the tank irrigation system in this study was evaluated using a Cropping Intensity indicator. This study reveals that Cropping Intensity was increased to more than 100% after rehabilitation of the tank irrigation system and is easily observed. Before rehabilitation of the tank, the average Cropping Intensity value was only 0.87. After rehabilitation of the tank, the average Cropping Intensity value increased to 1.20. The Cropping Intensity indicator is good for evaluating the modernization of the tank irrigation system. HIGHLIGHTS The study was carried out in crop calendar years from 2006–07 to 2017–18.; The performance of the tank irrigation system in this study was evaluated using a Cropping Intensity indicator.; Rehabilitation of the tank irrigation system is easily observed.; The average Cropping Intensity value is calculated.;